The Rehabilitation of Radicalized Youth in Swat: A Counter Terrorism Approach - Syeda Sidra Shah; Muhammad Wajeeh Shahrukh; Muhammad Adeel Khan, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
This research focuses on the rehabilitation of religiously radicalized youth in Pakistan, and two deradicalization and rehabilitation centers in Swat, namely the 'Sabaoon De-Radicalization Centre' and the 'Mishal Center for De-Radicalization,' were selected for this purpose. The purpose of this study was to identify the factors that contribute to youth radicalization; to learn about the rehabilitation approaches and processes used by government and private sector organizations in Pakistan; and to explore the success and failure of rehabilitation approaches and processes in selected rehabilitation centers in Pakistan. This work is based on qualitative data gathered through structured and semi-structured interviews, as well as Focused Group Discussions (FGDs) from 85 respondents from various segments of society, using purposive sampling. These respondents include reintegrated youth from de-radicalization centers, their families, de-radicalization center officials, influential members of society such as journalists, politicians, Village Defence Committee members, officials from civil and military administration, and members of the general public. The evidences from this research have suggested that the main reasons behind the radicalization of youth are poor socio-economic conditions, misinterpretation of the religion, lust to gain power, authority and prestige and a lot more.